Karakterisasi Suspensi Fitosom Ekstrak Kental Etanol Daun Binahong (Anredera cordifolia) Menggunakan Fosfatidilkolin - -, Hesti Purwaningsih; -, Muhammad Ilyas Nur Rachman; Yura Witsqa Firmansyah; Whisnu Ajie (Jurnal Serambi Engineering, 2025)
The benefits of binahong leaves (Anredera cordifolia) in the treatment of external wounds and as an anti-inflammatory agent can be optimised when used in topical form compared to the extract form. This research aims to determine the particle size characteristics and entrapment efficiency of the phytosome suspension of thick ethanol extract of binahong leaves using phosphatidylcholine via PSA and calculate the entrapment efficiency using the 1:1 formula. The research was carried out using a laboratory experimental method where the phytosome suspension was prepared by thin layer hydration. Phytosomes are a technology developed for the formulation of drugs and nutraceuticals containing hydrophilic active compounds from natural sources (such as herbs). This is achieved by complexing the active ingredients (phytoconstituents) with phospholipids. The resulting phytosomes typically have an average particle size of 50 nm to 500 µm, which is the result of complexation between the plant active ingredients and phosphatidylcholine. The phytosome suspension is prepared from a mixture of phytosome complex, ethanol and water, which has been subjected to thin layer hydration. The results of previous studies show that it is possible to prepare phytosome complex suspensions using natural materials and phosphatidylcholine carriers, with the resulting particle size characteristics and entrapment efficiency varying. The mean particle size of the phytosome suspension of the thick ethanol extract of Binahong leaves was 1.154 ± 0.745 µm with a polydispersity index of 0.416 and an entrapment efficiency value of 82.7140%.